Structural control of the hydrothermal system of the North-East Pyrénées (Corbières): Geothermal implications - Eude Adrien; Soliva Roger; Poprawski Yohann (BSGF - Earth Sciences Bulletin, 2025)
We investigate the hydrothermal system located at the North of the Pyrenean front forming a low relief area in a sedimentary environment (from the Mouthoumet Massif to the Montagne d’Alaric, Eastern-Pyrénées). This region is structured by W-E oriented Pyrenean folds and thrusts, which are affected by a dense network of NE-SW oriented fault system along which 24 hydrothermal springs localizes (>15 °C). Thanks to the construction of three balanced cross-sections and field-work campaigns, we infer that the structures abovementioned govern the hydrothermal system for the following reasons: 1) the Devonian carbonate layer confined between phyllosilicate rich formations constitutes the main fractured and karstified reservoir, 2) Pyrenean folds allows the main reservoir to outcrop at anticlines reliefs, favouring water recharge, flow at depth and high water column within low dipping limbs and synclines, 3) the Oligo-Miocene normal faults cut the fold and thrust structures and the phyllosilicate rich layers, and form dilatant high dipping pathways favoring the overpressured hydrothermal fluids to outflow at topographic depressions. The relatively low topography of the recharge area suggest that spring temperature is mainly controlled by reservoir depth, and therefore the folded and thrusted structure of the Devonian unit. This understanding of the reservoir geology and hydrothermal system provides new knowledge useful for geothermal exploration in polyphased-tectonics sedimentary environment.